All the Missiles Are One Missile Revisited: Dazzle in the Work of Zofia Kulik - Sarah Wilson (Arts, 2022)
This essay revisits one of Polish artist Zofia Kulik’s most important ‘photocarpets’, produced in a moment of hope, retrospection yet continuing war in 1993; seen by an international public in 1997. Visually, its composition is dominated by late Soviet sculptures symbolising Mother Russia and military aggression, yet the composition, ‘kilim-like’, with an additional reference to Polish Catholicism, involves bilateral and rotational symmetries which undermine significations of power and might with various other symbols: bodies, naked or draped, and Polish TV screenshots from both the military and entertainment worlds. ‘Dazzle’, the camouflage-related military term is also related to tears and (repressed) mourning. The female artist’s attitude to gender is crucial. The piece is both a ‘revisualisation’ and ‘rewriting’, relating both to the author’s previous texts on the artist from 1999 and 2001, and Kulik’s own rediscovery of her Ukrainian heritage, which reframes her own vision and understanding of the piece in 2022.